2005
DOI: 10.1254/jphs.fmj04005x5
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Pathophysiology of Proteinase-Activated Receptors (PARs): PAR-2-Mediated Proliferation of Colon Cancer Cell

Abstract: Abstract. Proteinase-activated receptor-2 (PAR-2) has been demonstrated to be highly expressed in the gastrointestinal tract. In the present minireview, we summarize the effects of PAR-1 and PAR-2 stimulation using their activating peptides and agonist proteinases on the calcium signaling and the cell proliferation in DLD-1 cell, a human colon cancer cell line. PAR-2 but not PAR-1 stimulation induced the enhancement of cell proliferation, whereas both PAR-1 and PAR-2 stimulation induced the transient increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…However, based on current literature it is fair to say that PAR-2 might be as important in tumor biology as is PAR-1. For instance, PAR-2 plays an important role in the invasion and growth of malignant neoplasms of the gastric [50,91,92] , colon [64,[93][94][95][96] , pancreas [97][98][99][100][101] , breast [102] and cervix [103] . Moreover, TF-dependent PAR-2 activation also contributes to experimental tumor metastasis in murine models [104] and PAR-2 blocking attenuates breast tumor growth [105] .…”
Section: Protease-activated Receptors Tumor Growth and Apoptosismentioning
confidence: 99%
“…However, based on current literature it is fair to say that PAR-2 might be as important in tumor biology as is PAR-1. For instance, PAR-2 plays an important role in the invasion and growth of malignant neoplasms of the gastric [50,91,92] , colon [64,[93][94][95][96] , pancreas [97][98][99][100][101] , breast [102] and cervix [103] . Moreover, TF-dependent PAR-2 activation also contributes to experimental tumor metastasis in murine models [104] and PAR-2 blocking attenuates breast tumor growth [105] .…”
Section: Protease-activated Receptors Tumor Growth and Apoptosismentioning
confidence: 99%
“…It has been reported that PAR 2 activation not only promotes cell proliferation (7, 9 -12) but also contributes to hypoxia-induced angiogenesis as well (13). Interestingly, PAR 2 and its activating proteinases are also expressed at the leading edge of cancer invasion (10,14), and its expression levels are tightly correlated with lymphatic metastasis in breast cancer and colorectal carcinoma (15,16). All these observations suggest that activation of PAR 2 promotes cell motility and facilitates tumor cell invasion.…”
mentioning
confidence: 96%
“…PAR 2 , one of the four members of this receptor family, can be activated by trypsin (3), tryptase (4), and the tumor-derived proteinase matriptase (5) to stimulate processes ranging from inflammation and pain perception to tumorigenesis (3,(7)(8)(9). Tumor cells, especially those of epithelial origin, express a high level of PAR 2 (10,11). Trypsin and matriptase are commonly overexpressed in tumor cells and in their microenvironment at concentrations compatible with PAR 2 activation (12,13).…”
mentioning
confidence: 99%